2020
DOI: 10.20944/preprints202011.0322.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Physical Activity on Obesity in Second Stage Pupils of Elementary Schools in the Region of Ústí nad Labem

Abstract: Obesity is a serious problem of our society. A long-term positive trend in body weight gain continues to persist. Paediatric obesity arises from a changed lifestyle of children, characterised by an important restriction of their spontaneous physical activity. A lack of physical activity is one of the most important causes of paediatric obesity associated with a number of serious disorders. The paper evaluates the effect of physical activity on obesity in second stage pupils of elementary schools in the region … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…According to Forýtková and Bourek [ 67 ], girls are more likely to spend their free time with friends or in hobby groups, but unfortunately, without sufficient physical activity, while boys have a closer inclination towards gaming technology and PC work. According to Pyšná et al [ 39 ], it is evident that with increasing age there is an increase in the time spent communicating on social networks, with social networks influencing many areas of people’s lives. The impact of virtual environments is being researched and discussed by experts across scientific disciplines.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Forýtková and Bourek [ 67 ], girls are more likely to spend their free time with friends or in hobby groups, but unfortunately, without sufficient physical activity, while boys have a closer inclination towards gaming technology and PC work. According to Pyšná et al [ 39 ], it is evident that with increasing age there is an increase in the time spent communicating on social networks, with social networks influencing many areas of people’s lives. The impact of virtual environments is being researched and discussed by experts across scientific disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…This trend follows a number of Czech and international studies. e.g., Pyšná et al [ 20 ], Kunešová et al [ 29 ], World Health Organization [ 59 ], National Institutes of Health in Prague [ 64 ], Caldeira et al [ 68 ], Flegal et al [ 69 ], Canadian Community Health Survey [ 70 ], Kubínová et al [ 71 ], and Pyšná et al [ 72 ]. In assessing the trend, it should be noted that already during the first stage of the research, we observed a relatively high proportion of children (33%) with other than normal weight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations